A Compound Faulting Model for the 1975 Kalapana, Hawaii, Earthquake, Landslide, and Tsunami. Issue 11 (6th November 2021) - Yamazaki, Yoshiki; Lay, Thorne; Cheung, Kwok Fai
Abstract: The Kalapana, Hawaii, M W 7.7 earthquake on November 29, 1975 generated a local tsunami with at least 14.3 m runup on the southeast shore of Hawaii Island adjacent to Kilauea Volcano. This was the largest locally generated tsunami since the great 1868 Ka'u earthquake located along‐shore to the southwest. Well‐recorded tide gauge and runup observations provide a key benchmark for studies of statewide tsunami hazards from actively deforming southeast Hawaii Island. However, the source process of the earthquake remains controversial, with coastal landsliding and/or offshore normal or thrust faulting mechanisms having been proposed to reconcile features of seismic, geodetic, and tsunami observations. We utilize these diverse observations for the 1975 Kalapana earthquake to deduce a compound faulting model that accounts for the overall tsunamigenesis, involving both landslide block faulting along the shore and slip on the island basal décollement. Thrust slip of 4.5–8.0 m on the offshore décollement produces moderate near‐field runup but controls the far‐field tsunami. The slip distribution implies that residual strain energy was available for the May 4, 2018 M W 7.2 thrust earthquake during the Kilauea‐East Rift Zone eruption. Local faulting below land contributes to geodetic and seismic observations, but is non‐tsunamigenic and not considered. Slip of 4–10 m on landslide‐like faults, which extend from the Hilina Fault Zone scarp to offshore shallowly dipping faults reaching near the seafloor, triples the near‐field tsunami runup. This compound model clarifies the roles of the faulting components in assessing tsunami hazards for the Hawaiian Islands. Plain Language Summary: On November 29, 1975, the Kalapana, Hawaii, earthquake with a seismic magnitude of 7.7 generated a tsunami reaching at least 14.3 m above sea level on the southeast shore of Hawaii Island adjacent to Kilauea Volcano. The largest locally generated event since the lesser documented, great 1868 Ka'u earthquake located to the southwest provides a key benchmark for studies of statewide tsunami hazards from volcanic activities on southeast Hawaii Island. We utilize seismic, tsunami, and land deformation observations to deduce the occurrence of both a massive block landslide from the Hilina Fault Zone and an offshore fracture along the island base during the earthquake. The inferred displacement of up to 8 m on the island base has moderate contributions to the local tsunami but controls the impact away from southeast Hawaii Island. The analysis suggests the1975 rupture left residual strain energy along the island base leading to the magnitude 7.2 earthquake during the Kilauea eruption on May 4, 2018. The up to 10 m displacement of the landslide block triples the local tsunami runup but with minor impacts away from Southeast Hawaii Island. This deduced earthquake mechanism clarifies the roles of landsliding and offshore fracturing in assessing tsunami hazards around the Hawaiian Islands. Key Points: Compound faulting on décollement and near‐surface crustal faults accounts for tsunami runup and tide gauge observations of the 1975 event Landslide block faulting extends from surface outcrops along the Hilina Fault System to 1–3 km deep shallowly dipping offshore faults Hilina block slide causes large near‐field coastal runup, while décollement slip dominates longer‐period far‐field tsunami excitation